2021
DOI: 10.1016/j.lfs.2021.119752
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation augments the suppressive effects of repurposed NF-κB inhibitors on ACE2 expression in human lung cell lines

Abstract: Aims Angiotensin-converting enzyme 2 (ACE2) is a key negative regulator of the renin-angiotensin system and also a major receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Here, we reveal a role for NF-κB in human lung cell expression of ACE2, and we further explore the potential utility of repurposing NF-κB inhibitors to downregulate ACE2. Main methods Expression of ACE2 was assessed by Western blotting and RT-qPCR in multiple human lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…IgM values in our patients have shown a negative correlation with serum zinc levels in females infected with SARS-CoV-2. Zinc augmented the suppressive effects of NF-κB on angiotensin-converting enzyme 2, a major receptor for SARS-CoV-2 infection [ 68 ], in a human lung cell line [ 69 ]. A study on hospitalized patients with COVID-19 in Iran has suggested that serum values of vitamin D, vitamin B12, and zinc at the time of admission negatively affect the clinical outcomes [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgM values in our patients have shown a negative correlation with serum zinc levels in females infected with SARS-CoV-2. Zinc augmented the suppressive effects of NF-κB on angiotensin-converting enzyme 2, a major receptor for SARS-CoV-2 infection [ 68 ], in a human lung cell line [ 69 ]. A study on hospitalized patients with COVID-19 in Iran has suggested that serum values of vitamin D, vitamin B12, and zinc at the time of admission negatively affect the clinical outcomes [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rnai I, et al indicated that nutritional intervention with Zn provided an adjutant therapy by eliciting their virucidal effects in the process of SARS-CoV-2 infection (80). Zn not only disrupted the balance of immune response, but also affected the expression of ACE2 receptors, which are required for SARS-CoV-2 entry into target cells (81). Moreover, Jennifer A Frontera, et al reported that Zn was associated with increased rates of recovery and reduced risk of mortality among COVID-19 patients (82).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that emetine alone could clearly reduce ACE2 mRNA and protein levels, but in the presence of zinc sulfate supplementation, emetine had more suppressive effects on ACE2 expression in H322M and Calu-3 cells. 59 …”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%